Medical Students’ Knowledge of Fertility Awareness-Based Methods of Family Planning - Danis, Peter G.; Kurz, Sally A.; Covert, Laura M. (Frontiers in Medicine, 2017)
ABSTRACT Medical Students’ Knowledge of Fertility-Awareness Based Methods of Family Planning OBJECTIVE: Traditional medical school curricula have not addressed fertility-awareness based methods of family planning. The objective of this study was to assess 1) third year medical students’ knowledge of fertility awareness-based methods (FABMs) of family planning, 2) their confidence in utilizing that knowledge in patient care, and 3) to implement focused education on FABMs to improve knowledge and confidence. METHODS: Third year medical students at one institution in the United States were given a ten-question assessment at the beginning of their OB-GYN rotation. Two lectures about FABMs and their clinical applications were given during the rotation. Students were given the same questions at the end of the rotation. Each questionnaire consisted of eight questions to assess a student’s knowledge of FABMs and two questions to assess the student’s confidence in sharing and utilizing that information in a clinical setting. McNemar’s test was used to analyze the data. RESULTS: 277 students completed a pre-test questionnaire and 196 students completed the post-test questionnaire. Medical knowledge improved from an initial test score of 38.99% to final test score of 53.57% (p < 0.05). Confidence in sharing FABM information with patients (0=very uncomfortable; 5=very comfortable) improved from 1.51 to 3.00 (P < 0.05). Confidence in utilizing FABM to diagnose and treat gynecologic/reproductive problems (0=not very confident and 5=very confident) improved from 1.01 to 3.15 (p < 0.05). CONCLUSIONS: Medical schools may not include FABMs in OB-GYN curriculum, however to patients, these methods remain a sought-after and valid form of family planning. This study shows that brief, focused education can increase medical students’ knowledge of and confidence with FABMs of family planning.